Medication review by a clinical pharmacist at the transfer point from ICU to ward: a randomized controlled trial. (12th August 2015) - Heselmans, A.; van Krieken, J.; Cootjans, S.; Nagels, K.; Filliers, D.; Dillen, K.; De Broe, S.; Ramaekers, D.
Summary What is known and objective Drug‐related problems (DRPs) occur frequently in hospitalized patients. Patient discharge from the intensive care unit (ICU) to a non‐ICU ward is one of the most challenging and high‐risk transitions of care due to the number of medications, and the complexity and acuity of the medical conditions that characterize this patient group. Pharmacists could play an important role in preventing DRPs. This study was undertaken to evaluate the impact on the number and severity of drug‐related problems by assigning a clinical pharmacist to the transfer process from ICU to wards. Methods The study was a randomized controlled multicentre trial conducted at the Hospital Network of Antwerp between December 2010 and January 2012. The clinical pharmacist performed a medical review in both the intervention and control group. Recommendations for drug therapy changes were immediately communicated in the intervention group but were kept blinded in the control group. The primary outcome was expressed as the number of implemented recommendations for drug therapy changes. Differences between groups were calculated using mixed effects binary logistic regression. Results Drug‐related problems were found in the medical records of 360 of the 600 participants (60%). A total of 743 recommendations could be made, 375 in the intervention group and 368 in the control group. 54·1% of these problems were adjusted on time in the intervention group vs. 12·8% in the control group. Of 743 recommendations, 24·8% were judged by the expert group as major, 13·1% as moderate, 53.4% as minor and 8·9% as having no clinical impact. The odds of implementing recommendations of drug therapy changes in the intervention group were 10 times the odds of implementing recommendations of drug therapy changes in the control group (odds ratio = 10·1; 95%CI [6·3–16·1]; P < 0·001), even after accounting for differences in types of DRP between the groups (odds ratio = 15·6; 95%CI [9·4–25·9]; P < 0·001). What is new and conclusion The integration of a clinical pharmacist at the transfer point from ICU to ward led to a significant reduction in DRPs.